2011
DOI: 10.3201/eid1702.101268
|View full text |Cite
|
Sign up to set email alerts
|

Possible Increased Pathogenicity of Pandemic (H1N1) 2009 Influenza Virus upon Reassortment

Abstract: Since emergence of the pandemic (H1N1) 2009 virus in April 2009, three influenza A viruses—seasonal (H3N2), seasonal (H1N1), and pandemic (H1N1) 2009—have circulated in humans. Genetic reassortment between these viruses could result in enhanced pathogenicity. We compared 4 reassortant viruses with favorable in vitro replication properties with the wild-type pandemic (H1N1) 2009 virus with respect to replication kinetics in vitro and pathogenicity and transmission in ferrets. Pandemic (H1N1) 2009 viruses contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 30 publications
(34 reference statements)
3
63
0
1
Order By: Relevance
“…This clade VII was represented by maximum number of isolates from geographically diverse areas. The tree topology was found similar as discussed earlier [19]. The clade VII, which is the largest clade is represented by H1N1pdm virus isolated from Japan, Mexico, China, Asia and several states of the USA.…”
Section: Phylogenetic Analysissupporting
confidence: 72%
See 1 more Smart Citation
“…This clade VII was represented by maximum number of isolates from geographically diverse areas. The tree topology was found similar as discussed earlier [19]. The clade VII, which is the largest clade is represented by H1N1pdm virus isolated from Japan, Mexico, China, Asia and several states of the USA.…”
Section: Phylogenetic Analysissupporting
confidence: 72%
“…With the number of reported pandemic cases of H1N1 virus in many parts of the world and continued viral persistence with elevated activity in India and nearby countries (Nepal, Sri Lanka, Bangladesh), has given an urgent need to track the global dispersion of this virus in humans. [18,19] but there was moderate number of H1N1pdm cases in 2012-2013. In this study, one Indian isolate with travel history confirmed by virus specific CPE, HA as well as CDC Real time RT-PCR was selected for complete HA gene characterization.…”
Section: Discussionmentioning
confidence: 96%
“…We first generated reassortant viruses by cotransfecting 293T cells with two complete sets of reverse genetics plasmids encoding the viral RNAs of MO and EN viruses as previously described (4,29). The supernatants of plasmid-transfected cells then were used for plaque assays on MDCK cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although the NA is grouped within the human-like H3N2 influenza lineage, North American triple reassortant SIVs containing a similar NA gene have been circulating in US swine herds for more than 5 years. Nev-ertheless, continuous circulation of pH1N1 in swine will increase the chance of further reassortment with human, avian or swine influenza viruses [9,17,22] and could result in a novel virus with the potential to cause infection and efficient transmission among humans. In conclusion, the emergence of novel reassortant H3N2 SIVs in US swine is further evidence of reassortment between pH1N1 and endemic SIVs.…”
mentioning
confidence: 99%